Thermal transfer in a multilayer plate with source of metabolic heat; MATEC Web of Conferences; Vol. 110 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2017) - Ulchiekov M. A. Mikhail (2017, 2017)
Title screen